ANALISIS KINERJA KEUANGAN PERUSAHAAN MAPA DALAM PERSPEKTIF PASAR MODAL INDONESIA - Ramadhani, Balqish Nabilah; Prayoga, Dedek; Hamzah, Muamar (Journal Economic Management and Business, 2025)
This study analyzes the financial performance of PT Mitra Adiperkasa Tbk (MAPA) from a capital market perspective, focusing on key issues related to stock price volatility and investment potential. The main objectives of the study are to evaluate MAPA's financial performance based on market indicators, as well as to identify buy and sell signals using Moving Average Convergence Divergence (MACD). The research method involves analyzing historical MAPA stock price data and calculating the MACD indicator. The results of the study indicate that MACD can provide a relevant indication of MAPA's stock price momentum, although it needs to be considered together with the company's fundamental factors and overall market conditions. The implications of this study provide guidance for investors in making investment decisions in the capital market, especially related to retail sector stocks, and highlight the importance of technical analysis as a complement to fundamental analysis.